Comparative analysis of the clinical aspects of colorectal cancer in young adult and older adult patients in Saudi Arabia - Aldriwesh, Marwh G.; Aljaian, Amer R.; Alorf, Khalid M.; Bayounis, Mohammed A.; Alrayani, Yazeed H.; Philip, Winnie; Algarni, Mohammed; Alselaim, Nahar A.; Alotibi, Raniah S. (Frontiers in Oncology, 2024)
IntroductionRecent studies have shown an increase in the prevalence of early-onset colorectal cancer (CRC) in people aged 20–49 compared to those aged 50–74, with a more rapid increase in the younger age groups. Poorly differentiated, left-sided, and rectal tumors were more common in young adults than in older adult CRC patients. We aimed to improve the understanding of early-onset CRC and to guide primary care physicians on strategies to mitigate its impact.MethodsAdult patients with CRC identified within 2015–2022 were recruited and divided into young adult-onset (CRC identified at age ≤49 years) and older adult-onset (CRC identified at age ≥50 years). Clinical data were retrieved from electronic medical records, then analyzed. Multivariable analyses were performed to predict the CRC prognosis in both age groups.ResultsThe study cohort had 530 patients categorized into young adult (n=98; 18.5%) and older adult (n=432; 81.5%). Higher proportions of family histories of CRC, other malignancies, and inflammatory bowel disease in the young adult group were observed (P<0.05). Gastrointestinal symptoms mainly abdominal pain and nausea were more often identified in the young adults. Mucinous adenocarcinoma, signet ring cells, and poorly differentiated tumors were higher in the young adults (P<0.05). Lymphovascular invasion was an independent predictor for advanced stage CRC (AOR 8.638, 95%CI 2.152–34.673, P=0.002 for young adults and AOR 21.757, 95%CI 10.025–47.219, P=0.001 for older adults). Further, the mucinous (AOR 3.727, 95%CI 1.937–7.173, P=0.001 for young adults and AOR 3.534, 95%CI 1.698–7.354, P=0.001 for older adults) and lymphovascular invasion (AOR 3.371, 95%CI 2.107–5.393, P=0.001 for young adults and AOR 3.246, 95%CI 1.910–5.517, P=0.001 for older adults) were independent predictors for recurrence/late metastasis in both age groups.ConclusionWe recommended to raise awareness among healthcare providers of the importance of lowering the threshold of suspicion in young people presenting with worrisome gastrointestinal symptoms. Our findings suggested the importance of reconsidering the current CRC screening guidelines to lower the threshold of the recommended starting age.